A three‐phase excess post‐exercise oxygen consumption in Atlantic salmon Salmo salar and its response to exercise training. Issue 5 (9th March 2018) - Zhang, Y.; Claireaux, G.; Takle, H.; Jørgensen, S. M.; Farrell, A. P.
Abstract : The recovery of oxygen uptake to the standard metabolic rate (SMR) following exhaustive chasing exercise in Atlantic salmon Salmo salar parr occurred in three phases (rapid, plateau and slow). The initial recovery phase lasted 0·7 h and contributed 16% to the total excess post‐exercise oxygen consumption (EPOC). It was followed by a longer plateau phase that contributed 53% to the total EPOC. The slow recovery phase that completed recovery of SMR, which has not been reported previously, made a 31% contribution to the total EPOC. The plasticity of EPOC was demonstrated in exercise‐trained fish. Exercise training increased EPOC by 39% when compared with control fish (mean ± S.E., 877·7 ± 73·1 v . 629·2 ± 53·4 mg O2 kg −1, d.f. = 9, P <  0·05), with the duration of the plateau phase increasing by 38% (4·7 ± 0·58 v . 3·4 ± 0·16 h, d.f. = 9, P <  0·05) and the contribution of the slow phase to the total EPOC increasing by 80% (173·9 ± 23·9 v . 312·5 ± 50·4 mg O2 kg −1, d.f. = 9, P  < 0·05). As a result, the combination of the plateau and slow phases of exercise‐trained fish increased by 47% compared with control fish (756·6 ± 71·4 v . 513·6 ± 43·1 mg O2 kg −1 ; d.f. = 9, P  = 0·01). To substantiate the hypothesis that the plateau and slow recovery phase of EPOC was related to general metabolic recovery following exhaustive exercise, the time‐course for recovery of SMR was compared with previously published metabolite recovery profiles. The final phase of metabolic recovery was temporally associated with the final phases of gluconeogenesis, lactate oxidation and muscle intracellular pH regulation. Therefore, the plasticity of the latter phase of EPOC agreed with the known effects of exercise training in fishes.